Prevalence and Predictors of Depression among Type 2 Diabetes Mellitus Outpatients in Eastern Province, Saudi Arabia - Elmahalli, Azza Ali (International Journal of Health Sciences, 2015)
Objectives: Diabetes Mellitus is frequently accompanied by serious complications. Less known is the increased risk for depression. Undiagnosed depression prevents initiation of treatment, thereby contributing to poor clinical outcomes. Study aimed to determine prevalence and predictors of depression among type 2 diabetes mellitus patients. Methodology: Study was cross- sectional. It was conducted in the outpatient clinics of diabetes mellitus in a government hospital in Eastern Province, Saudi Arabia in 2013. Patients with type 2 diabetes mellitus (260 participants) were selected using systematic random sampling technique. One interview questionnaire was designed to collect demographic and health factors. Two self- administered instruments were used to assess perceived social support and depression. Assessment of the relationship between depression and its predictors was done using Univariate analysis. Multivariable analysis was used to evaluate the combined effect of several factors associated with depression among type 2 diabetes mellitus patients after adjusting for confounding variables. Results: Almost fifty percent of diabetics were depressed (49.6%). Patients with poor diabetes mellitus control (OR 3.221, P .000) and unmarried (OR 3.206, P .025 ) were more risky for developing depression and difference was significant. Conclusion: Type 2 diabetes mellitus was associated with depression. So, diabetics should be regularly examined for signs and symptoms of depression.